2020
DOI: 10.1007/s11739-020-02599-3
|View full text |Cite
|
Sign up to set email alerts
|

Early emergency readmission frequency as an indicator of short-, medium- and long-term mortality post-discharge from hospital

Abstract: Frequent emergency readmissions, an indicator of quality of care, has been rising in England but the underlying reasons remain unclear. We examined the association of early readmissions with subsequent mortality in adults, taking into account the underlying presenting diagnoses and hospital length of stay (LOS). Data of alive-discharge episodes were prospectively collected between 01/04/2017 and 31/03/2019 in an National Health Service hospital, comprising 32,270 patients (46.1% men) aged 18–107 years (mean = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…We found that being a frequent user was significantly associated with an increased risk of mortality with frequent users of EDs having a 95% increased mortality followed by frequent users of hospitals (67% higher), frequent users of GPs (50% higher) and frequent users of medical specialists (44% higher). Our mortality risk results were slightly lower than other studies investigating outcomes of frequent users of EDs and hospitals on mortality rates, although many of these studies are not community‐based 25,26 . A systematic review by Moe et al, which summarised evidence from 31 studies, found that frequent users of EDs are at increased odds of death of around 2.2 25 .…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…We found that being a frequent user was significantly associated with an increased risk of mortality with frequent users of EDs having a 95% increased mortality followed by frequent users of hospitals (67% higher), frequent users of GPs (50% higher) and frequent users of medical specialists (44% higher). Our mortality risk results were slightly lower than other studies investigating outcomes of frequent users of EDs and hospitals on mortality rates, although many of these studies are not community‐based 25,26 . A systematic review by Moe et al, which summarised evidence from 31 studies, found that frequent users of EDs are at increased odds of death of around 2.2 25 .…”
Section: Discussioncontrasting
confidence: 76%
“…There were also some factors that were less likely to be associated with frequent users across services, such as adequate physical activity, reporting good quality of life and consuming 1–13 alcoholic drinks per week. Reporting poorer or lower quality of life was supported by evidence that frequent users of medical specialists, EDs and hospitalisations were more likely to report poorer health 13,14,26 . With regard to consuming 1–13 alcoholic drinks per week, there is growing evidence that low to moderate alcohol consumption is protective as people age, 24 although it is not clear if the benefit is because of the ethanol or the social and pleasurable benefits of drinking alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We aimed to investigate if MAIT cells may be associated with COPD morbidity. As a measure of morbidity, we chose all-cause hospitalization during the 3-year follow-up because it is a strictly objective outcome that is easily measured, associated with considerable healthcare costs and strongly linked to mortality [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the age and gender information of the discharged and deceased patients were also recorded with HİIMS. Because as seen in hospital discharge and mortality studies, age, gender, and frequency of admission were taken into account (Heppleston E,et al [6,7]). In this respect, our study is compatible with the literature.…”
Section: Introductionmentioning
confidence: 99%